HEMOGLOBIN-ALBUMIN CO-POLYMERS FOR BLOOD SUBSTITUTES: INCREASING THE REPRODUCIBILITY OF THE POLYMERIZATION REACTION - SCURTU, Florina; ȚEBREAN, Bogdan; ÁRKOSI, Mariann Kinga; IONELE, Adrian; SILAGHI-DUMITRESCU, Radu (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Reticulation/polymerization of proteins using bifunctional reagents, with glutaraldehyde as a typical example, has a wide range of applications – of which HBOC (hemoglobin/hemerythrin based oxygen carriers) are illustrative. Here, the kinetics of the derivatization reaction of hemoglobin and albumin with glutaraldehyde are revisited, in order to establish the optimal conditions such as concentration of protein and derivatization agent for which the final product can be a reasonable candidate for blood substitutes. A purpose-built mixing device is described, which allows automated mixing of up to four reagents in less than 100 milliseconds, allowing for polymers with a more reproducible molecular weight.